A model code for the radiative theta pinch - Lee, Sing; Saw, Sor Heoh; Lee, Paul Choon Keat; Akel, M.; Damideh, Vahid; Khattak, N. A. D.; Mongkolnavin, R.; Paosawatyanyong, B. (AIP Publishing, 2014)
A model for the theta pinch is presented with three modelled phases of radial inward shock phase, reflected shock phase, and a final pinch phase. The governing equations for the phases are derived incorporating thermodynamics and radiation and radiation-coupled dynamics in the pinch phase. A code is written incorporating correction for the effects of transit delay of small disturbing speeds and the effects of plasma self-absorption on the radiation. Two model parameters are incorporated into the model, the coupling coefficient f between the primary loop current and the induced plasma current and the mass swept up factor fm. These values are taken from experiments carried out in the Chulalongkorn theta pinch.